Comparative effects of combined use of alcohol with cannabis and tobacco on testicular function in rats. Issue 4 (29th June 2021) - Nwonuma, Charles Obiora; Osemwegie, Osarenkhoe Omorefosa; Irokanulo, Emenike Onyebum; Alejolowo, Omokolade Oluwaseyi; Kayode, Omowumi Titilola; Olaolu, Tomilola Debby; Ada, Adakole Sylvanus; Rotimi, Damilare Emmanuel; Maimako, Roltdelmwa Filibus; Adedayo, Adeyinka Samuel; Ojo, Oluwafemi Adeleke
Abstract: Alcoholism has been linked to problems with male reproductive function. The combined effects of alcohol, cannabis, and tobacco were compared in this study. A total of 35 rats were assigned randomly into seven groups A–G: animals in A were administered distilled water. Animals in B–G were either administered alcohol orally (30 ml 40% alcohol) or exposed to smoke from ignited tobacco (exposure to smoke from 0.7 g tobacco for 5 min) or cannabis (exposure to smoke from 0.7 g tobacco and cannabis for 5 min): B (orally administered alcohol), C (exposed to the smoke from tobacco), D (exposed to smoke from cannabis), E (treated with alcohol and exposed to smoke from tobacco), F (treated with alcohol and exposed to smoke from cannabis), G (treated with alcohol and exposed to smokes from tobacco and cannabis). Assays were carried on the testicular homogenate after a 14-day treatment. There was a significant increase in activity of alkaline phosphatase ( P  ≤ 0.05), concentrations of cholesterol, glutathione reductase, and malondialdehyde in treated rats by the co-administration of alcohol with cannabis and tobacco compared with the control group. The combined treatment also caused degeneration and morphological distortions of testicular cells. The biochemical and histoarchitectural change was due to oxidative damage attributable to the synergistic effects. The high binding energy of tetrahydrocannabinol ligand to prostate acid phosphatase may be a prediction that the ligand can have an inhibitory effect on the function of enzymes in the prostate.